Barriers to early detection of cognitive impairment in the elderly despite the availability of simple cognitive screening tools and the pharmacist's role in early detection and referral. (5th July 2017) - Abed, Howraa; Ball, Patrick; Morrissey, Hana
Abstract: Aim: The aim of this review is to identify a suitable cognitive screening tool that can be used by the pharmacist during home medication review in addition to calculating the medications' total anticholinergic burden (ACB). Data sources: A search of the literature was conducted using PubMed, Embase, Medline and Google Scholar databases to identify relevant studies using the following keywords: 'cognitive impairment', 'cognitive impairment AND diagnosis', 'cognitive scales', 'dementia', 'delirium', 'pharmacist role', 'mini‐mental state examination (MMSE)', 'the Rowland dementia assessment scale (RUDAS)', 'the Alzheimer's Disease Assessment Scale ‐ Cognition (ADAS‐Cog)' and 'barriers and problems'. Only informational websites, clinical trials and review articles were included. Results: The MMSE, RUDAS, ADAS‐Cog, Psychogeriatric Assessment Scale (PAS) and Kimberley Indigenous Cognitive Assessment (KICA‐Cog) require specialist training. The anxiety and depression checklist (K10) and 'worried about your memory' (WAYM) can be self‐administered without prior training. The ACB scoring system can also be used to determine the total medications ACB. Conclusion: The K10 and WAYM can be used by the pharmacist during medication reviews to detect cognitive impairment early and refer the elderly for further medical care supported by the calculated score for the patient's total medications' ACB.